Investigation of enhanced external counter pulsation of blood pressure-elevating effect on chronic heart failure patients with low blood pressure - Bingxu, Chen; Shi Jie; Qiu Quan; Jiang Wing; Gan Qinjing; Qiu Yuangang; Chen Jie (Journal of the Pakistan Medical Association, 2025)
Objectives: To explore and evaluate the clinical effect of enhanced external counter pulsation in the treatment of patients with chronic heart failure and low blood pressure. Method: The retrospective study was conducted from January, 1, 2023, to January 31, 2024, at the Department of Cardiology, The First Affiliated Hospital of Zhejiang Chinese Medical University, China, and comprised data from January to October 2023 of chronic heart failure in patients who also had low blood pressure. The patients were divided into two groups on the basis of the treatment received. Group A patients had been treated with enhanced external counter pulsation, while group B patients had been asked to do regular exercises. Both the groups had been treated for cumulatively 35 hours. The change in blood pressure was the main outcome measure, and it was measure at baseline and 24h after treatment. Data was analysed using SPSS 20. Results: Of the 111 patients, 61(55%) were in group A; 36(59%) females and 25(41%) males with mean age 59.33±9.01 years. There were 50(45%) patients in group B; 29(58%) females and 21(42%) males with mean age 56.47±11.23 years. Baseline systolic blood pressure was not significantly different between the groups (p>0.05). Post-intervention, both the groups showed significant increase in in systolic blood pressure (p<0.05), but the change from baseline was more significant in group A compared to group B (p<0.05). Conclusion: Enhanced external counter pulsation had a significantly better therapeutic effect in the treatment of patients with chronic heart failure and low blood pressure. Key Words: Enhanced external counter pulsation, Heart failure, Low blood pressure, Cardiac rehabilitation.